Archive and/as Montage in The City as Text: Exposing the Chilean Social Uprising - Tessa Oliveira (MatLit, 2025)
In October 2019, a government-issued increase in Santiago’s subway fares served as the spark that ignited a widespread uprising against Sebastián Piñera’s rightwing regime and, more broadly, against the brutal inequalities of the neoliberal system installed during the U.S.-backed dictatorship of Augusto Pinochet and maintained over the last three decades by institutional political parties and the ruling classes. As the voices of the uprising overtly indicated, “It’s not 30 pesos, it’s 30 years.” Following the dictatorship—among pacts of silence, proclamations of an already reconciled future, and insufficient, incomplete processes of justice and reparation—cultural production has played an important role in establishing relationships with the past that do not monumentalize or silence its anachronistic overflows. It is in this context that I read La Ciudad como Texto (The City as Text), created by Carola Ureta Marín, which registers the graphic expressions of the Chilean social uprising, digitally displaying a photomontage of the graffitied walls of the Alameda on the thirty-sixth day of protests alongside thirty-six texts that were added to the montage in the form of “footnotes”. I propose that, by exposing temporalities, authorships, and media to one another, and by exposing the narrative construction and deliberate mediation at play in historical representation, The City as Text fulfills the critical task that Derrida entrusts to fiction: to attest to the anarchic secret of the archive in ways that allow us to think its prosthetic nature and its aporias. It is this anarchic condition—this dependence on an exterior supplement—that grants the archive its redemptive possibility, the promise it makes to the future in rendering a past event (il)legible. These supplemental technologies make events of reading possible, readings that produce the originary moment and expose the voids it leaves for the future, readings that bring the event’s possibilities and valences into appearance. I suggest that it is through the particular modality of montage that The City as Text proliferates events of reading, treating the archive not as “the site of a narrative but a site for denarrativization; not a region for understanding but a space for exposure,” (Moreiras 10).